Membangun Pendidikan Islam Berbasis Entrepreneurship Dalam Meningkatkan Motivasi Kemandirian Santri di Pondok Pesantren Ashabul Yamin Lasi - Akmal Hadi; Zulfani Sesmiarni (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to produce a design in the form of an entrepreneurship-based education guide and independence of students at the Ashhabul Yamin Islamic Boarding School based in Lasi Village, Candung District, Agam Regency, West Sumatra. This study uses a qualitative research type with a descriptive approach. Data were obtained from observations, interviews, and documentation. Data analysis used data condensation, data presentation, and drawing conclusions. The results of the study indicate that the Ashabul Yamin Lasi Islamic Boarding School enables the realization of student independence through entrepreneurship education. The agricultural sector, especially oranges and bananas, is one of the fields currently being promoted for entrepreneurship education. The Ashabul Yamin Lasi Islamic Boarding School starts from the planning stage to the implementation of plantation activities. The Ashabul Yamin Lasi Islamic Boarding School begins activities by planning, setting goals, collecting data and information, and creating a number of activities to achieve goals, namely that these activities must be adjusted to opportunities and potential. Full support from the Islamic boarding school, both founders, administrators, and the active involvement of students and local residents in helping to manage and develop the Islamic boarding school business unit.